ANALISIS EFEKTIVITAS MENGAJAR GURU PASCA KEBIJAKAN PEMBATASAN PENGGUNAAN PONSEL: STUDI KASUS DI SMAN 2 PANDEGLANG - Ahmad Jajang Jajuli; Delia Ayunda Maulia; Finka Alayda; Aura Shafa Nabila; M. Paisal Bahari; Azahra Ulfah; Galuh Mulyawan (STKIP Pesisir Selatan, 2026)
Policies related to mobile phone use in schools are generally studied more from the perspective of their impact on students, while the perspective of teachers as implementers of learning is still rarely researched. This study aims to assess the effectiveness of teacher teaching after the implementation of the mobile phone policy through Circular Letter No. 100.3.4.1 / 0374-Dindikbud / 2026 at SMAN 2 Pandeglang. The method used is a quantitative descriptive approach with a case study design, involving 32 teachers from various subjects through a clear questionnaire. The results show that this policy is considered very effective in improving teacher teaching performance, especially in aspects of classroom control and a conducive learning atmosphere (85.31%) and focus and time management (84.21%). In addition, there was an increase in teacher-student interaction, such as more intense eye contact and more active discussions. However, teachers still face obstacles in quick access to materials and the need to adapt technology-based learning methods.